GREEN MARKETING STRATEGIES, CUSTOMER SATISFACTION, REGULATORY FRAMEWORKS AND CUSTOMER LOYALTY IN MANUFACTURING FIRMS IN NAIROBI CITY COUNTY, KENYA - ANGELYNE MUTHONI MWABU (Machakos University Press, 2025)
The manufacturing sector is a key driver of socio-economic growth but also a major contributor to environmental degradation through its activities, processes, and products. In response to evolving consumer demands and sustainability pressures, manufacturing firms are increasingly adopting Green Marketing (GM) strategies to reduce environmental impacts while enhancing customer satisfaction and loyalty. These strategies promote environmental protection while creating new markets and employment opportunities. However, their influence within Kenya’s manufacturing sector remains underexplored, and the extent of their impact on firm performance and sustainability is not well understood. The overall objective of this study was to establish how GM strategies, green customer satisfaction (GCS) and regulatory frameworks (RF) affect green customer loyalty in the manufacturing firms in Nairobi City County of Kenya. The specific objectives were to: establish the influence of green product quality on green customer loyalty in the manufacturing firms in Nairobi City County; determine the influence of green price on customer loyalty; assess the influence of green promotion on customer loyalty; establish the influence of green corporate image on customer loyalty; evaluate the extent to which green customer satisfaction intervenes in the relationship between GM strategies and customer loyalty; establish the moderating effect of regulatory frameworks on the relationship between GM strategies and customer loyalty; and determine the joint effect of GM strategies, green customer satisfaction and regulatory frameworks on customer loyalty. The study was anchored on the diffusion of innovation, expectancy disconfirmation paradigm and stakeholders’ theories. The descriptive cross sectional survey design was employed using a target population of 725 manufacturing firms in the County from which a sample of 258 respondents was drawn. A pilot study of 20 randomly selected firms was conducted to test the reliability and validity of the research instruments. A self-administered questionnaire and interview guide were used to collect data. Descriptive and inferential statistics were generated, including percentages for profiling, the Chi-square for testing variable relationships, and the ordinal logistic regression to test hypotheses at a 5% significance level. The findings revealed that green product quality significantly influenced customer loyalty (β = 0.804, p = 0.007), indicating that perceived environmental and functional quality drives loyalty. However, green price, promotion, and corporate image did not show any statistically significant effects on loyalty (β = – 0.337, p = 0.403; β = 0.373, p = 0.197; β = –0.034, p = 0.428). Green customer satisfaction was found to significantly mediate the relationship between GM strategies and loyalty (β for GCS = 2.488, p = 0.000; β for GM = 0.887, p = 0.041). Although Regulatory frameworks had a strong independent effect (β = 1.652, p = 0.000), it did not significantly moderate the relationship (β = –0.147, p = 0.445). In the joint model, all three predictors significantly influenced loyalty, with customer satisfaction (β = 2.512, p = 0.000) and Regulatory frameworks (β = 1.743, p = 0.000) having positive impacts. However, GM strategies had a significant negative coefficient (β = –1.298, p = 0.007). The study concludes that customer loyalty is best achieved through quality green products, genuine customer satisfaction, and credible regulatory compliance. While GM strategies like price and promotion play supportive roles, they are insufficient on their own in influencing customer loyalty. The study suggests that in order to enhance customer loyalty, manufacturing firms need to adopt integrated strategies that align product quality, transparent pricing, and authentic promotion with customer expectations and existing regulatory standards.